Factors affecting repurchase intention with customer engagement as intervening variables in B2B context - Putri, Negina Kencono (Mednarodno inovativno poslovanje, 2023)
The goal of this research is to learn more about the impact of customer satisfaction., social CRM, customer perceived value, on repurchase intention. This research is survey research on consumers of construction companies specifically in this case manufacturing companies in Indonesia.
Keywords: customer engagement; customer perceived value; customer satisfaction; družbeni CRM; namera ponovnega nakupa; repurchase intention; social CRM; sodelovanje strank; Trženje; Vedenje potrošnikov; zadovoljstvo strank; zaznana vrednost strank